Civil Society and the Democratization of Communications in Latin America - María Soledad Segura (Íconos)
Despite the fact that disputes over communications policies in Latin America seem to be restricted to confrontations between governments and media corporations, civil society organizations have to an unprecedented degree been protagonists in policy debate and formulation. We re-construct the conditions that made it possible for civil society to push reforms in communication policies in the region and we characterize these organizations and their proposals. We cover their achievements in terms of influence in regulations in this area, as well as challenges that this new situation implies for them. Also, we propose theoretic problems that are derived from this analysis – civil society and its links to the state and the market, its influence in processes of defining public policies, the relation between media and politics, and communication democracy.